BOSHLANG‘ICH TA’LIMDA MUSIQA MADANIYATI DARSLARI ORQALI IJODIY TAFAKKURNI RIVOJLANTIRISH (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
This article discusses the development of creative thinking in primary school students through music culture lessons. The importance of music education in shaping children’s aesthetic taste, independent thinking, and creative abilities is analyzed. The effectiveness of using interactive methods and innovative technologies in music classes is also highlighted.